2022
DOI: 10.3390/jcm11051260
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of a Novel Multifunctional Amorphous Hydrogel Containing Olea europaea Leaf Extract (EHO-85) for the Treatment of Skin Ulcers: A Randomized, Active-Controlled Clinical Trial

Abstract: This 8-week, multicenter, randomized, active-controlled, observer-blinded clinical trial was designed to demonstrate the accelerating effect on wound healing of the novel Olea europaea leaf extract hydrogel (EHO-85) by comparing it to a widely used amorphous hydrogel. Results showed that EHO-85 significantly accelerated wound healing, regardless of ulcer etiology (pressure, venous leg or diabetic foot) and prognosis, doubling the median wound area reduction compared with a reference amorphous hydrogel (79.4% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…Regardless of their aetiology, a greater number of patients achieved good results after application of the extracts in hydrogel form, with a significant reduction in the wound area and an acceleration of the healing process compared to that of the control. 128,129…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of their aetiology, a greater number of patients achieved good results after application of the extracts in hydrogel form, with a significant reduction in the wound area and an acceleration of the healing process compared to that of the control. 128,129…”
Section: Resultsmentioning
confidence: 99%
“…127 Olea europaea leaf extract hydrogel (EHO- 85) In vivo (human subjects/both sexes): this clinical trial observed that EHO-85 accelerated wound healing regardless of ulcer etiology by modulating reactive oxygen species and pH. 128…”
Section: Olive Leaf Extracts (Ole) With Microparticles Of Hyaluronic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, reduction in ulcer area was reported in six studies 72,74,75,77,79,80 of which only two 72,77 found an apparent improvement in comparison to the control. Again, these were at high risk of bias.…”
Section: Topical Herbal or Traditional Medicinal Preparationsmentioning
confidence: 93%
“…Rationale: We found nine RCTs which reported on the use of topica herbal or traditional medicinal preparations, which fulfiled our inclusion criteria. [72][73][74][75][76][77][78][79][80] Of seven studies reporting on complete wound healing, [72][73][74][75][76][77]79 all were at moderate or high risk of bias, and any positive effects on wound healing should be interpreted cautiously.…”
Section: Topical Phenytoinmentioning
confidence: 99%